'UNITING AGAINST IMPUNITY: THE UN GENERAL ASSEMBLY AS A CATALYST FOR ACTION AT THE ICC'. Issue 4 (11th September 2017) - Ramsden, Michael; Hamilton, Tomas
Abstract: This article evaluates the role of the UN General Assembly ('UNGA') and its subsidiary organs in acting as a catalyst for action at the International Criminal Court ('ICC'). The power of the UN Security Council ('UNSC') to make a referral to the ICC has been increasingly challenged in recent years, due to the perceived misuse of the veto by permanent members and general failings to enforce international criminal law in the face of documented atrocities. Meanwhile, the UNGA and its subsidiary organs have exerted meaningful pressure on the UNSC through the creation of commissions of inquiry and country-specific resolutions. There is the possibility for the UNGA to engage in dialogue with the ICC through 'quasi-judicial' resolutions, in coordinating collective responses to a recalcitrant State and individual perpetrators and also through the possible assumption of a referral power. This analysis reveals that the UNGA has become increasingly active in international justice and holds the potential for an enhanced role in addressing the failings of the current UNSC-dominated paradigm governing UN–ICC relations, thereby facilitating States in 'uniting against impunity'.